2015
DOI: 10.1016/j.jmps.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

A generalized spherical harmonic deconvolution to obtain texture of cubic materials from ultrasonic wave speed

Abstract: In this paper, the spherical harmonic convolution approach for HCP materials [1] is extended into a generalised form for the principal purpose of bulk texture determination in cubic polycrystals from ultrasonic wave speed measurements. It is demonstrated that the wave speed function of a general single crystal convolves with the polycrystal Orientation Distribution Function (ODF) to make the resultant polycrystal wave speed function such that when the three functions are expressed in harmonic expansions, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This technique is also useful in determining the grain size along with the crystallographic texture of the material, for which primarily the change in wave velocity, amplitude, and attenuation coefficient have been analyzed 17,18 . The use of ultrasound waves has been further evolved as the general convolution approach for validation of its capability to capture the bulk crystallographic texture information [19][20][21] . These studies have consistently reported qualitative comparison of ultrasound technique in line with EBSD and neutron diffraction outcome.…”
mentioning
confidence: 99%
“…This technique is also useful in determining the grain size along with the crystallographic texture of the material, for which primarily the change in wave velocity, amplitude, and attenuation coefficient have been analyzed 17,18 . The use of ultrasound waves has been further evolved as the general convolution approach for validation of its capability to capture the bulk crystallographic texture information [19][20][21] . These studies have consistently reported qualitative comparison of ultrasound technique in line with EBSD and neutron diffraction outcome.…”
mentioning
confidence: 99%
“…[44], for an overview). Recently, an intrinsically well-posed inverse problem for determining the ODF was developed by Lan et al [44,89] and later validated against neutron diffraction experiments [90,91]. The method relies on averaging the monocrystal phase-velocity function, Vifalse(kfalse^false), over the ODF to construct the polycrystalline phase-velocity function, Vifalse(kfalse^false).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, analytical attempts have been made to understand wave scattering behaviour and to characterize a material's grain orientation distribution based on elastic wave propagation, 10,11 experiments were conducted 12,13 and with the help of advanced computational capabilities, numerical modelling or Finite Element (FE) approaches have been developed to tackle the same problem. 14,15 Most numerical modelling involved a 2-dimensional (2D) Voronoi-based microstructure, which only considered in-plane rotation of the grains, as a 3D microstructure demands more computational resources. To date, there has been a notable absence of investigations into the impact of increasing texture intensity on the propagation of elastic waves.…”
Section: Literature Surveymentioning
confidence: 99%